Periosteum and fascia lata: Are they so different? - Manon, Julie; Evrard, Robin; Maistriaux, Louis; Fievé, Lies; Heller, Ugo; Magnin, Delphine; Boisson, Jean; Kadlub, Natacha; Schubert, Thomas; Lengelé, Benoît; Behets, Catherine; Cornu, Olivier (Frontiers in Bioengineering and Biotechnology, 2022)
Introduction: The human fascia lata (HFL) is used widely in reconstructive surgery in indications other than fracture repair. The goal of this study was to compare microscopic, molecular, and mechanical properties of HFL and periosteum (HP) from a bone tissue engineering perspective. Material and Methods: Cadaveric HP and HFL (N = 4 each) microscopic morphology was characterized using histology and immunohistochemistry (IHC), and the extracellular matrix (ECM) ultrastructure assessed by means of scanning electron microscopy (SEM). DNA, collagen, elastin, glycosaminoglycans, major histocompatibility complex Type 1, and bone morphogenetic protein (BMP) contents were quantified. HP (N = 6) and HFL (N = 11) were submitted to stretch tests. Results: Histology and IHC highlighted similarities (Type I collagen fibers and two-layer organization) but also differences (fiber thickness and compaction and cell type) between both tissues, as confirmed using SEM. The collagen content was statistically higher in HFL than HP (735 vs. 160.2 μg/mg dry weight, respectively, p < 0.0001). On the contrary, DNA content was lower in HFL than HP (404.75 vs. 1,102.2 μg/mg dry weight, respectively, p = 0.0032), as was the immunogenic potential (p = 0.0033). BMP-2 and BMP-7 contents did not differ between both tissues (p = 0.132 and p = 0.699, respectively). HFL supported a significantly higher tension stress than HP. Conclusion: HP and HFL display morphological differences, despite their similar molecular ECM components. The stronger stretching resistance of HFL can specifically be explained by its higher collagen content. However, HFL contains many fewer cells and is less immunogenic than HP, as latter is rich in periosteal stem cells. In conclusion, HFL is likely suitable to replace HP architecture to confer a guide for bone consolidation, with an absence of osteogenicity. This study could pave the way to a bio-engineered periosteum built from HFL.